Penerapan Konsep Data Warehouse Untuk Pemantauan PeneiImaan PBB - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Presently, PBB (land and building tax) revenue has an important role in local government. Therefore, it is necessary to get sufficient information about the realization of the revenue. One of the problems related to this task is the difficulty to monitor the amount of the tax already paid by the taxpayers. This happens because of the large number of the tax objects to be managed. This research attempts at resolving the problem by applying data warehouse concept. In this case, tables associated with revenues available in SISMIOP (Property Tax Information and Management System) database are transferred into the data warehouse. This was done by extracting, transforming, and integrating the tables. Data in the warehouse were structured into "cubes" which consisted of "dimensions" and "fact table". To process and manipulate the data, the Microsoft Data Analyzer package program was used. The results showed that the more dimensions were used, the more detailed the information could be acquired and presented. This made the PBB revenue monitoring can be conducted in more detailed for each part, including regions, years, assessment books, KPPBB (local land and building tax service office) , and JPB (type of building utilization).